Social-LCA. Methodological proposal applied to physical activity program implementation into old people's routines - Flor-Montalvo, Francisco Javier; García-Alcaráz, Jorge Luis; Sánchez-Toledo Ledesma, Agustín; Álvarez-Kurogi, Leandro (Sustainability (Switzerland), 2020)
Progressive population aging and life expectancy increase in Spain, resulting from medical and social improvements, have put this population segment in a privileged position for the implementation of new methodologies aimed at improving the quality of life of the elderly. Social life cycle analysis (S-LCA) is a widely studied technique to evaluate the social and environmental impacts generated by a product, service, or process. Throughout this paper, S-LCA is applied to the implementation of physical activity programs in routines for older people, allowing a complete evaluation of the impact of such activities. From this study, it is deduced that the execution phase of the program is the one that causes the most positive impact. Design and programming have a much more notable impact than expected. With regard to the involved categories, the user is the greatest beneficiary of the implementation of these programs, although the local community and administration are other interest groups that will highly benefit, although the impact will be much less than in the case of users.
Keywords: social assessment; social sustainability; elderly; physical activity; social life cycle analysis (S-LCA); Scopus; JCR